EVALUATION ON THE IMPLEMENTATION PROGRAM OF NON-PERMANENT EDUCATORS ASSIGNATION AT THE EDUCATIONAL UNITS IN ALOR REGENCY - alboin selly (LPPM Universitas Negeri Jakarta, 2019)
Abstract: This study aims to evaluate the implementation of assignation program of non-permanent educators by the Educational Department in Alor using the CSE-UCLA model which consist of four stages namely needs assessment, program planning, formative evaluation and summative evaluation. A descriptive-qualitative method was applied with interview techniques, questionnaires,and documentation for the data collection. Based on the component of needs assessment, the program has a clear legal basis. However, since there is no technical guidance, therefore a different interpretation occurs during the implementation. Based on the program planning, the educational department has a program plan while the school needs aspect has not been fulfilled in terms of education degree and field of study. Formative evaluation, the assignation criteria for educators is based on school proposals using the administrative selection system. The placement of educators is not in accordance with the needs of schools based on the subject course. Summative evaluation, achievement of the program objectives has been attained in terms of quantity, although the improvements in terms of quality of assignation and placement of educatorare needed to be a concern to meet the school’ needs